High Modulus Conductive Hydrogels Enhance In Vitro Maturation and Contractile Function of Primary Cardiomyocytes for Uses in Drug Screening. Issue 24 (22nd November 2018) - Wu, Fengxin; Gao, Aijun; Liu, Jian; Shen, Yaoyi; Xu, Panpan; Meng, Jie; Wen, Tao; Xu, Lianghua; Xu, Haiyan
Abstract: Effective and quick screening and cardiotoxicity assessment are very crucial for drug development. Here, a novel composite hydrogel composed of carbon fibers (CFs) with high conductivity and modulus with polyvinyl alcohol (PVA) is reported. The conductivity of the composite hydrogel PVA/CFs is similar to that of natural heart tissue, and the elastic modulus is close to that of natural heart tissue during systole, due to the incorporation of CFs. PVA/CFs remarkably enhance the maturation of neonatal rat cardiomyocytes (NRCM) in vitro by upregulating the expression of α‐actinin, troponin T, and connexin‐43, activating the signaling pathway of α5 and β1 integrin‐dependent ILK/p‐AKT, and increasing the level of RhoA and hypoxia‐inducible factor‐1α. As a result, the engineered cell sheet–like constructs NRCM@PVA/CFs display much more synchronous, stable, and robust beating behavior than NRCM@PVA. When exposed to doxorubicin or isoprenaline, NRCM@PVA/CFs can retain effective beating for much longer time or change the contractile rate much faster than NRCM@PVA, respectively, therefore representing a promising heart‐like platform for in vitro drug screening and cardiotoxicity assessment. Abstract : High modulus conductive hydrogels are fabricated using carbon fibers and polyvinyl alcohol, which enhance the maturation and electrophysiological performance of neonatal rat cardiomyocytes in vitro, by activating the α5β1 integrin signaling pathway and upregulating RhoA and hypoxia inducible factor‐1α (HIF‐1α). The cell–hydrogel constructs effectively respond to drugs modulating cardiomyocytes' contraction, exhibiting high potential for uses in drug screening and cardiotoxicity assessment.